Design, Synthesis, In Vitro, and Initial In Vivo Evaluation of Heterobivalent Peptidic Ligands Targeting Both NPY(Y1)- and GRP-Receptors-An Improvement for Breast Cancer Imaging? - Alicia Vall-Sagarra; Shanna Litau; Clemens Decristoforo; Björn Wängler; Ralf Schirrmacher; Gert Fricker; Carmen Wängler (MDPI AG, 2018)
Heterobivalent peptidic ligands (HBPLs), designed to address two different receptors independently, are highly promising tumor imaging agents. For example, breast cancer has been shown to concomitantly and complementarily overexpress the neuropeptide Y receptor subtype 1 (NPY(Y1)R) as well as the gastrin-releasing peptide receptor (GRPR). Thus, radiolabeled HBPLs being able to bind these two receptors should exhibit an improved tumor targeting efficiency compared to monospecific ligands. We developed here such bispecific HBPLs and radiolabeled them with 68Ga, achieving high radiochemical yields, purities, and molar activities. We evaluated the HBPLs and their monospecific reference peptides in vitro regarding stability and uptake into different breast cancer cell lines and found that the 68Ga-HBPLs were efficiently taken up via the GRPR. We also performed in vivo PET/CT imaging and ex vivo biodistribution studies in T-47D tumor-bearing mice for the most promising 68Ga-HBPL and compared the results to those obtained for its scrambled analogs. The tumors could easily be visualized by the newly developed 68Ga-HBPL and considerably higher tumor uptakes and tumor-to-background ratios were obtained compared to the scrambled analogs in and ex vivo. These results demonstrate the general feasibility of the approach to use bispecific radioligands for in vivo imaging of breast cancer.